Determination of Mechanical Properties of Slurry Infiltrated Steel Fiber Concrete Using Fly Ash and Metakaolin - A.P, Shelorkar; P.D, Jadhao (International Journal of Engineering and Technology, 2018)
This paper reports on a wide-ranging study on the properties of slurry infiltrated fiber concrete containing fly ash, Metakaolin, and hook ended steel fibers. Properties studied include workability of fresh slurry infiltrated fiber concrete, and compressive strength, flexural tensile strength, splitting tensile strength, dynamic elasticity modulus, impact energy of hardened slurry infiltrated fiber concrete. Fly ash and Metakaolin content used was 0%, 2.5%, 5.0%, 7.5% and 10% in mass basis, and hook ended steel fibers volume fraction was 0%, 2.0%, 3.0% and 4.0% in volume basis. The laboratory results showed that steel fiber addition, either into control concrete or fly ash, Metakaolin blend slurry infiltrated fiber concrete; improve the tensile strength properties, flexural strength, impact energy and modulus of elasticity. In this experimental study, compressive strength improvement ratio is 33.60%, and Structural efficiency is 9.50 % higher in slurry infiltrated fiber-concrete with Metakaolin as compared with fly ash based slurry infiltrated fiber concrete at the 4% replacement ratio of hook ended steel fibers by volume.Â Â